THE USE OF WORD WALL APPLICATION AS LEARNING MEDIA TO IMPROVE THE STUDENTS’ ENGLISH VOCABUULARY MASTERY AT SMK HANDAYANI MAKASSAR - Syahrir, Andi Ahmad; Noni, Nurdin; Munir, Munir (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
The objective of this research was to evaluate whether the Word Wall application effectively improves students' English vocabulary mastery. Typically, teaching aids and applications aim to make learning more engaging and motivating. This study used a pre-experimental design with pre-test and post-test measurements to assess the impact of the Word Wall application. Conducted at SMK Handayani Makassar with 96 tenth-grade students, the research focused on a sample of 23 students from Class X TBSM-TKR, selected through cluster random sampling. The data, analyzed using a paired samples t-test, showed an increase in mean scores from 68.52 in the pre-test to 90.00 in the post-test. With a significance value (2-tailed) of 0.00, which is less than 0.05, the results indicate that the Word Wall application was effective in enhancing students' vocabulary mastery.Student perceptions of the Word Wall application were positive, reflecting its effectiveness in improving English vocabulary mastery. According to the previous chapter, students' mean score was 51.04 with a standard deviation of 2.40, suggesting that the application increased student motivation by making the learning process more engaging, reducing boredom, and fostering greater interest and enthusiasm for vocabulary learning.Keywords: Word Wall Application, Learning Media, and Vocabulary Mastery